2022
DOI: 10.1186/s12957-022-02748-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of APOE gene ε4 allele on serum lipid profiles and risk of cardiovascular disease and tumorigenesis in southern Chinese population

Abstract: Background Human apolipoprotein E (APOE) polymorphisms are attributable to the presence of three common alleles, namely, ε2, ε3, and ε4, which generate six genotypes, viz, E2/E2, E2/E3, E3/E3, E3/E4, E4/E4, and E2/E4. APOE polymorphisms are associated with all types of tumors and cardiovascular diseases (CVD). However, the relationship between the type of APOE polymorphisms and tumorigenesis remains debatable. Therefore, we aimed to investigate the role of APOE polymorphisms on the tumor with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…ApoE*ε4 has been shown to influence total cholesterol and LDL cholesterol even at lower body mass indices (BMIs) [ 59 ]. Other studies have shown that ApoE*ε4+ carriers in comparison to non-carriers have higher levels of TC, TG and LDL [ 60 , 61 ], which is consistent with our findings. Another study has found that among HIV-positive patients who are ApoE*ε4 carriers, there is an elevation of TC, LDL-C, and TG which is associated with faster rates of cognitive decline [ 62 ].…”
Section: Discussionsupporting
confidence: 93%
“…ApoE*ε4 has been shown to influence total cholesterol and LDL cholesterol even at lower body mass indices (BMIs) [ 59 ]. Other studies have shown that ApoE*ε4+ carriers in comparison to non-carriers have higher levels of TC, TG and LDL [ 60 , 61 ], which is consistent with our findings. Another study has found that among HIV-positive patients who are ApoE*ε4 carriers, there is an elevation of TC, LDL-C, and TG which is associated with faster rates of cognitive decline [ 62 ].…”
Section: Discussionsupporting
confidence: 93%
“…It could be due to the higher number of CAD cases as compared to controls in their studies. 25,[42][43][44] In the meantime, our study on other CAD lipidassociated risk factors revealed that LPA gene copy number >2 (gain) was higher in YAMI patients while 1 copy number (loss) of the LPA gene was higher in controls although there was no significant association.…”
Section: Discussionmentioning
confidence: 73%
“…In those circumstances, physicians should consider the data the CK ratio provides. For example, since glucose [ 39 ] and lipid metabolism correlate closely with both PC tumorigenesis and cardiovascular health, a sizable proportion of cancer patients also experience heart disease [ 40 ]. For patients with a high CK ratio, it is necessary to determine whether the high CK ratio is primarily caused by an abnormally high CK-MB level resulting from myocardial damage or due to a low total CK related to tumors as mentioned above.…”
Section: Discussionmentioning
confidence: 99%